PENERAPAN PERMAINAN PASARAN DALAM PEMBELAJARAN MATEMATIKA MATERI POKOK ARITMATIKA SOSIAL - Rini Utami (Delta: Jurnal Ilmiah Pendidikan Matematika, 2013)
This study aims to determine the differences in learning achievement are influenced by the use of mathematics permainan pasaran learning models with conventional learning models in the teaching and learning of Mathematics . The study population was all students of class III consists of three classes . Sample of two classes, namely class IIIB with a number of students as class 36 and class IIIA experiment with 37 students as the number of control class . Random sampling technique with a group ( cluster random sampling ) . Methods of data collection with the test methods and documentation . Analyzes were performed with the prerequisit normality Liliefors and homogeneity Bartlet . Data were analyzed by analysis of covariance ( Anacova ) with initial ability as a control variable . Test results with α = 5 % showed a significant difference in improvement in mathematics learning achievement are influenced by the use of permainan pasaran learning models. Math learning achievement using the permainan pasaran learning model of learning the game better than learning mathematics achievement using conventional learning models on material social arithmatic.